Improvement of the simulation of the summer East Asian westerly jet from CMIP5 to CMIP6 - Yuanhai FU; Zhongda LIN; Dong GUO (Atmospheric and Oceanic Science Letters, 2020)
The East Asian westerly jet (EAJ) plays a crucial role in affecting the East Asian summer rainfall (EASR). Therefore, evaluations of EAJ simulations are vital for improving the understanding and projections of climate change in East Asia. This study evaluates the simulations of the climatology and interannual variability in the present-day summer EAJ in the CMIP6 models and compares the results with those in the CMIP5 models by analyzing the historical climate simulations of 29 CMIP5 models and 21 CMIP6 models during the period from 1986–2005. In general, the CMIP6 models capture the EAJ more realistically than the CMIP5 models. The results show that the CMIP6 models reasonably capture the spatial features of the climatological zonal wind at 200 hPa and simulate a smaller zonal wind bias along the EAJ. The locations of the EAJ’s core are at the observed location in nearly all CMIP6 models but in only approximately two-thirds of the CMIP5 models. The EAJ’s intensity is closer to the observed value and exhibits a smaller intermodel dispersion in the CMIP6 models. The CMIP6 models also show an improved ability to reproduce the interannual variability in the EAJ’s meridional displacement and have a stronger relationship with the EASR.